Peranan Kepemimpinan Transformasional, Persepsi Gender, dan Dukungan Sosial Terhadap Intensi Berwirausaha Mahasiswa - Butarbutar, Daniel; Suwarno, Henky Lisan (Value : Jurnal Manajemen dan Akuntansi, 2025)
Entrepreneurial intention among university students is shaped by various psychological and social factors, making it a crucial topic in the evolving landscape of education and employment This study explores how transformational leadership, gender perception, and social support influence entrepreneurial intention among university students. In a rapidly changing economy, where job opportunities are uncertain, students need strong motivation, resilience, and access to supportive networks to pursue entrepreneurship. This study investigates the influence of transformational leadership, gender perception, and social support on students’ entrepreneurial intentions, highlighting the role of mentorship, equality perceptions, and social encouragement in fostering business aspirations. A survey of 150 students was conducted to analyze the interplay between these factors. The findings reveal that transformational leadership and social support significantly enhance students' entrepreneurial motivation, while gender perceptions reflect evolving views on equality in business. This study provides practical insights for educators and policymakers to create supportive environments that empower young entrepreneurs. By strengthening leadership in education and expanding social support systems, higher education can contribute to the vision of “Indonesia Emas 2045” by fostering a generation of innovative, resilient, and competitive entrepreneurs.